التعويضات المالية عن الطلاق التعسفي دراسة مقارنة بين الفقه الإسلامي واقانون الأسرة الجزائري - يوسف نصرات; حفيظ قتال (University of eloued جامعة الوادي, 2025)
"تهدف هذه الدراسة إلى بحث وتحليل مسألة التعويضات المالية عن الطلاق التعسفي"" في دراسة مقارنة بين الفقه الإسلامي وقانون الأسرة الجزائري. تنطلق الدراسة من إشكالية تحديد مدى التوافق أو الاختلاف بين النظامين في تأصيل ومعالجة هذا النوع من التعويض، وتحديد طبيعته وعلاقته بالمستحقات المالية الأخرى للمطلقة. ولمعالجة هذه الإشكالية، اتبعت الدراسة المنهج الوصفي التحليلي والمنهج المقارن. وقد تم تقسيمها إلى ثلاثة مباحث رئيسية، بالإضافة إلى مقدمة وخاتمة. تناول المبحث الأول مفهوم الطلاق التعسفي (تعريفه، حكمه، شروطه، صوره) في الفقه والقانون. وعالج المبحث الثاني فكرة التعويض عن هذا الطلاق، حيث تم تعريف التعويض، ثم استعراض موقف الفقه الإسلامي الذي يعالج جبر الضرر عبر آليات كالمتعة وقواعد الضمان، وموقف قانون الأسرة الجزائري الذي أقر تعويضاً صريحاً مستقلاً (المادة 52) من الامر 05/02 ، مع عقد مقارنة بينهما. أما المبحث الثالث، فقد خصص لدراسة علاقة هذا التعويض بالمستحقات المالية الأخرى للمطلقة (المتعة، نفقة العدة، نفقة الإهمال، الصداق المؤجل)، مبيناً استقلالية التعويض عن هذه الحقوق في القانون الجزائري، والطبيعة المختلفة لكل منها في الفقه والقانون. وخلصت الدراسة إلى مجموعة من النتائج، أبرزها: اتفاق الفقه والقانون على ذم الطلاق التعسفي وضرورة جبر ضرر المطلقة؛ اعتماد الفقه على آليات المتعة وقواعد الضمان بمرونة، بينما اعتمد القانون الجزائري آلية التعويض القضائي المباشر ؛ استقلالية التعويض عن الطلاق التعسفي في القانون الجزائري عن باقي الحقوق المالية للمطلقة. واختتمت الدراسة بتق"ديم بعض التوصيات العلمية والعملية المتعلقة بتعزيز حماية المطلقة وتوحيد الاجتهاد القضائي في هذا المجال This study aims to investigate and analyze the issue of Financial Compensation for Arbitrary Divorce through a comparative study between Islamic Jurisprudence (Fiqh) and Algerian Family Law. The study addresses the problematic of determining the extent of convergence or divergence between the two systems in conceptualizing and addressing this type of compensation, defining its nature, and its relationship with other financial entitlements of the divorced woman. To tackle this problematic, the study employed descriptive-analytical and comparative methodologies. It was divided into three main chapters, in addition to an introduction and a conclusion. The first chapter dealt with the concept of arbitrary divorce (definition, ruling, conditions, forms) in Fiqh and law. The second chapter addressed the idea of compensation for this divorce, defining compensation, then reviewing the position of Islamic Fiqh, which handles redress through mechanisms like Mut'a (consolatory gift) and rules of Daman (liability/guarantee), and the position of Algerian Family Law, which established explicit, independent compensation (Article 52) based on tort liability, followed by a comparison between them. The third chapter was dedicated to examining the relationship between this compensation and other financial entitlements of the divorced woman (Mut'a, Nafaqat al-'Idda (waiting period alimony), maintenance arrears, deferred dowry), demonstrating the independence of the compensation from these rights in Algerian law and the distinct nature of each in Fiqh and law. The study reached several conclusions, most notably: the agreement between Fiqh and law on condemning arbitrary divorce and the necessity of compensating the divorced woman for harm; Fiqh's reliance on the flexible mechanisms of Mut'a and Daman rules, whereas Algerian law adopted the direct judicial compensation mechanism based on fault and damage; the independence of compensation for arbitrary divorce in Algerian law from the divorced woman's other financial rights. The study concluded by offering some academic and practical recommendations related to enhancing the protection of divorced women and unifying judicial practice in this area."
Keywords: الطلاق التعسفي قانون الأسرة الجزائري الفقه الإسلامي التعويض المالي; Arbitrary Divorce; Financial Compensation; Islamic Jurisprudence (Fiqh); Algerian Family Law; Mut'a (Consolatory Gift); Moral Damages; Divorced Woman's Rights; Comparative Study.